Effects of Viscous Dissipation and Radiation on MHD Natural Convection in Oblique Porous Cavity with Constant Heat Flux (Advances in Applied Mathematics and Mechanics, 2018)
Effects of viscous dissipation and radiation on MHD natural convection inoblique porous cavity with constant heat flux is studied numerically in the presentarticle. The right inclined wall is maintained at a constant cold temperature $T_c$ andthe left inclined wall has a constant heat flux $q$ with length $S$, while the remainderof the left wall is adiabatic. The horizontal walls are assumed to be adiabatic. Thegoverning equations are obtained by applying the Darcy model and Boussinesq approximations.COMSOL's finite element method is used to solve the non-dimensionalgoverning equations together with specified boundary conditions. The governing parametersof this study are Rayleigh number ($Ra$=10,100,200,250,500 and 1000), Hartmannnumber (0 ≤ $Ha$ ≤ 20), inclination angle of the magnetic field ($0^◦$≤ $ω$ ≤ $π/2$),Radiation (0≤ $R$ ≤15), the heater flux length (0.1≤ $H$ ≤1) and inclination angle of thesloping wall (−$π$/3 ≤ $φ$ ≤ $π$/3). The results are considered for various values of thegoverning parameters in terms of streamlines, isotherms and average Nusselt number.It is found that the intensity of the streamlines and the isotherm patterns decrease withan increment in Hartmann number. The overall heat transfer is significantly increasedwith the increment of the viscous dissipation and the radiation parameters.